2016
DOI: 10.1038/srep29722
|View full text |Cite
|
Sign up to set email alerts
|

Proposed correlation of structure network inherited from producing techniques and deformation behavior for Ni-Ti-Mo metallic glasses via atomistic simulations

Abstract: Based on the newly constructed n-body potential of Ni-Ti-Mo system, Molecular Dynamics and Monte Carlo simulations predict an energetically favored glass formation region and an optimal composition sub-region with the highest glass-forming ability. In order to compare the producing techniques between liquid melt quenching (LMQ) and solid-state amorphization (SSA), inherent hierarchical structure and its effect on mechanical property were clarified via atomistic simulations. It is revealed that both producing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…To date, various techniques for measuring the mechanical behaviors and properties of individual NWs have been developed, such as in situ bending tests 11 , tensile tests 12 15 , resonant frequency tests 16 and nanoindentation 17 , and investigations on the mechanical properties of the NWs have been reported in the literature. Lieber et al .…”
Section: Introductionmentioning
confidence: 99%
“…To date, various techniques for measuring the mechanical behaviors and properties of individual NWs have been developed, such as in situ bending tests 11 , tensile tests 12 15 , resonant frequency tests 16 and nanoindentation 17 , and investigations on the mechanical properties of the NWs have been reported in the literature. Lieber et al .…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the so-called local atomic shear strain, η i Mises [56], denotes the atomic motions in local regions under stress and is related to the density of shear transformations [57,58]. Meanwhile, the atomic motions probably affect the distribution of free volumes.…”
Section: Resultsmentioning
confidence: 99%
“…One parameter to describe the degree of connectivity of the network is the average coordination number N , defined as the number of nearest-neighboring pairs that each icosahedral center forms with other icosahedral centers [53,54]. Based on a cutoff distance of 3.2 Å, at which the first peak of g(r) vanishes [see Fig.…”
Section: Fractal Cluster Network In Al 90 Sm 10mentioning
confidence: 99%